Asymptomatic COVID‐19 infection in late pregnancy indicated no vertical transmission. Issue 9 (30th April 2020) - Lu, Dawei; Sang, Lin; Du, Shihua; Li, Tao; Chang, Yange; Yang, Xiu‐An
Abstract: This study is to investigate the clinical characteristics of late pregnancy with asymptomatic 2019 novel coronavirus disease (COVID‐19) infection, evaluate the outcome of maternal and fetal prognosis, and identify the evidence of intrauterine vertical transmission. A 22‐years‐old pregnant woman with asymptomatic COVID‐19 infection who was admitted to our hospital on 11 February 2020 was enrolled in this study. Clinical data including laboratory test results and chest computed tomography (CT) scanning were collected and reviewed. Diagnosis of late pregnancy with asymptomatic COVID‐19 infection was made. Lumbar anesthesia for cesarean section was performed and a female baby was delivered uneventfully, with the Apgar score of 9 to 10 points. Three times of COVID‐19 nucleic acid test for the baby was negative after delivery. The puerpera returned to normal after the operation and two times of throat swab COVID‐19 nucleic acid test were all negative after antiviral therapy. We reported an asymptomatic COVID‐19 pregnant woman with detailed clinical information and our result indicated that for late pregnant women with asymptomatic COVID‐19 infection, there might be no intrauterine infection caused by vertical transmission. Highlights: We show a timely case report regarding the current COVID‐19 outbreak. Pregnant woman with asymptomatic COVID‐19 infection was prensented in detail.